2007
DOI: 10.1111/j.1365-2648.2007.4304.x
|View full text |Cite
|
Sign up to set email alerts
|

Caring for older people with dementia in residential care: nursing students’ experiences

Abstract: Better preparation and support are needed for students on placements involving residents with dementia. Feasible strategies for more effective support include increased curriculum content about caring for people with dementia, and improved collaboration between university schools of nursing and settings for care of older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 32 publications
1
55
1
Order By: Relevance
“…Minimising developed over time with repeated exposure and protected participants from exhaustion. However, Robinson and Cubit (2007) highlight difficulties associated with this including inadvertently placing students in risky situations without prior knowledge which was raised as a potential issue for staff in this study (i.e., blasé attitudes).…”
Section: Dealing Withmentioning
confidence: 94%
“…Minimising developed over time with repeated exposure and protected participants from exhaustion. However, Robinson and Cubit (2007) highlight difficulties associated with this including inadvertently placing students in risky situations without prior knowledge which was raised as a potential issue for staff in this study (i.e., blasé attitudes).…”
Section: Dealing Withmentioning
confidence: 94%
“…Direct contact or immersion in practice without prior preparation was not sufficient as it can lead to feelings of inhibition and intimidation when interacting with people with dementia (Robinson & Cubit, 2007). All the studies that included both theoretical sessions and practice experience in their interventions showed a positive effect in both qualitative and quantitative data in relation to the levels of comfort when interacting with people with dementia.…”
Section: Accepted M Manuscript Evalmentioning
confidence: 99%
“…In contrast, based on thematic analysis of focus group interviews Robinson and Cubit (2007) found that intimidation and fear were common feelings amongst students completing a 3-week placement in residential elder care facilities without prior training or preparation. From the weekly focus group discussions, students reported feeling inhibited in communicating with residents as well as with experienced mentors, therefore their support needs were not met.…”
Section: Accepted Manuscript Evaluation Of Dementia Education Programmentioning
confidence: 99%
See 2 more Smart Citations